Perbandingan Profil Lipid dan Penanda Inflamasi pada Pria Obesitas dan Non-Obesitas - Dinutanayo, Wimba Widagdho; Akhriyani, Mayesti (Poltekkes Kemenkes Tanjung Karang, 2021)
Obesity is a global health problem suffered by people around the world, including Indonesian. Adipose tissue dysfunction and fat distribution are affecting the incidence of obesity-related diseases. The study aimed to compare the levels of lipid profiles (total cholesterol, HDL, LDL, and triglycerides) and inflammatory markers (ESR and leukocyte count) between groups with normal nutritional status and obesity. Data were collected using a cross-sectional study with 14 young adult men for the normal nutritional status group with a BMI of 18,5-24,99kg/m2 and 14 young adult men for the obese group with a BMI ³25 kg/m2 in August-December 2019. The respondents aged 18-35 years were measured body composition and tested for levels of lipid profiles and inflammatory markers. The results of statistical tests with independent t-test showed no difference in the number of leukocytes (p-value=0.08) but there was a significant difference in ESR (25,1±14,1 vs 47,2±23,7,p-value=0,006), total cholesterol (126,6±26,4 vs 175,5±32,0, p-value=0,001), triglycerides (113,3±38,3 vs 161,5±46,9,p=0,006) and LDL (53±18,4 vs 95±27,3, p-value=0,001). This study concludes that there are significant differences in levels of total cholesterol, triglycerides, LDL, and ESR between groups of individuals with normal nutritional status and obesity.